Review of A* (A Star) Navigation Mesh Pathfinding as the Alternative of Artificial Intelligent for Ghosts Agent on the Pacman Game - Zikky, Moh. (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
Shortest pathfinding problem has become a populer issue in Gameâs Artificial Intelligent (AI). This paper discussed the effective way to optimize the shortest pathfinding problem, namely Navigation Mesh (NavMesh). This method is very interesting because it has a large area of implementation, especially in games world. In this paper, NavMesh was implemented by using A* (A star) algorithm and examined in Unity 3D game engine. A* was an effective algorithm in shortest pathfinding problem because its optimization was made with effective tracing using segmentation line. Pac-Man game was chosen as the example of the shortest pathfinding by using NavMesh in Unity 3D. A* algorithm was implemented on the enemies of Pac-Man (three ghosts),Â which path was designed by using NavMesh concept. Thus, the movement of ghosts in catching Pac-Man was the result of this review of the effectiveness of this concept. In further research, this method could be implemented on several optimization programmes, such as Geographic Information System (GIS), robotics, and statistics.